Pre-plant and pre-emergence herbicides for weed management in transplanted rice - Jalindar, Mote Kishor; Lourduraj, A Christopher; Arthanari, P Murali; Chandrasekhar, C N; Sudhakara, T M; Ragothuman, G (Indian Journal of Plant Protection, 2020)
The study on pre-plant and pre-emergence herbicide weed management in transplanted rice during Rabi 2011-12 at Tamil Nadu Agricultural University, Coimbatore revealed that pre-plant application of glyphosate 0.75 kg a.i. ha-1 recorded higher mean grain yield (5766 kg ha-1), lower weed density (3.2, 6.7 and 5.6 m-2 at 20,40 and 60 DAT), dry weight (2.0, 3.7 and 4.1 g m-2 at 20,40 and 60 DAT) and weed control efficiency (71,5, 69.5 and 69.2 % at 20,40 and 60 DAT) compared to non application of glyphosate. The application of pre-plant glyphosate eliminated most existing vegetation and prevented weed establishment. In main field among the different treatments early post emergence (EPOE) application of Bensulfuron methyl+ pretilachloar (6.6 GR) at 0.06+0.60 kg /ha recorded significantly higher grain yield (6450 kg ha-1), straw yield (8614 kg ha-1) through better weed control efficiency as indicated by lower weed density (4.3,5.5 and 4.6 m-2 at 20 ,40 and 60 DAT), reduced weed dry matter (2.2,3.4 and 3.0 g m-2 at 20 ,40 and 60 DAT) and higher weed control efficiency (80.6,83.2 and 85.0% at 20,40 and 60 DAT) followed by PE application of Pretilachlor at 0.75 a.i.Kg ha-1 + HW at 40 DAT other treatments. This is due to better control of pre emerged weeds and as well as emerging weeds as it has a high level of activity against broad leaved weeds and sedges. Pre-plant application of glyphosate 0.75 kg a.i ha-1 recorded highest net return (`25,188/ha) compared to non glyphosate application (`/ha 22,579). Among the different herbicides, EPOE Bensulfuron methyl + pretilachlor (6.6 GR) at 10 DAT registered higher gross returns (`/ha. 59,318 ha-1), net return (`/ha. 33, 120 ha-1) and B: C ratio (2.19).